PLASMA β-SECRETASE1 (BACE1) LEVELS AS MARKER OF COGNITIVE FUNCTION DECLINE IN ELDERLY - Syahfira A Syahna; Muhammad Ichwan; Nuraiza Meutia; Jelita Siregar; Zulham Yamamoto (Talenta Publisher, 2023)
BACE1 which forms amyloid plaques consisting of amyloid β peptides is a typical neuropathological lesion in the brain of Alzheimer's disease. Many studies have shown that β-amyloid is central to the pathophysiology of Alzheimer's disease and may play an early role in neurodegenerative disorders. The BACE1 enzyme forms amyloid β plaques. The BACE1 protein is detectable in plasma and its levels are significantly increased in patients with mild cognitive impairment and future Alzheimer's. This Aβ peptide accumulates into senile plaques causing the characteristics of Alzheimer's disease, can cause neuronal death and cognitive decline